2018
DOI: 10.1371/journal.pone.0205133
|View full text |Cite
|
Sign up to set email alerts
|

Did you choose appropriate tracer for retrograde tracing of retinal ganglion cells? The differences between cholera toxin subunit B and Fluorogold

Abstract: Cholera toxin subunit B (CTB) and Fluorogold(FG) are two widely utilized retrograde tracers to assess the number and function of retinal ganglion cells (RGCs). However, the relative advantages and disadvantages of these tracers remain unclear, which may lead to their inappropriate application. In this study, we compared these tracers by separately injecting the tracer into the superior Colliculi (SC) in rats, one or 2 weeks later, the rats were sacrificed, and their retinas, brains, and optic nerves were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Retrograde tracing techniques allow us to: (1) assess neuronal connections between a target population of neurons and their inputs throughout the nervous system, (2) identify the connection from their source through to their point of termination . In general, retrograde tracing can be achieved using viral neuronal tracer (VNT), such as rabies virus (RV) and pseudo RV that are transported to the cell body via axonal dynein . However, VNT can spread quickly and cause degradation of neural tissue.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Retrograde tracing techniques allow us to: (1) assess neuronal connections between a target population of neurons and their inputs throughout the nervous system, (2) identify the connection from their source through to their point of termination . In general, retrograde tracing can be achieved using viral neuronal tracer (VNT), such as rabies virus (RV) and pseudo RV that are transported to the cell body via axonal dynein . However, VNT can spread quickly and cause degradation of neural tissue.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…There are two main structurally important working mechanisms: (1) small organic molecular tracers: it forms a DNA complex in the nucleus with fluorescence enhancement after endocytosis, (2) dextran‐based tracers: a specific molecular weight (10 kDa) of dextran tends to stay in the intracellular cytosol of neural cells. Retrogradely injected tracers use axonal transport to move from the distal region (axonal branches responsible for signal transduction) of neural cell to the cell body …”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the ability of B5 toxoids to undergo retrograde transport in neurons has led to extensive use of CTBconjugates as neuronal tracers. [16][17][18] Tinker et al previously demonstrated that by mimicking the full-length holotoxin, fluorescent CT chimeras could be produced by replacing the toxic A1 domain with a fluorescent protein. 19 Chen et al expanded on this work by expressing fusions with heat-labile enterotoxin IIA, and showing that these could be successfully delivered to the cytosol of neurons in mammalian cell culture.…”
Section: Introductionmentioning
confidence: 99%